2011
DOI: 10.1021/ja205867f
|View full text |Cite
|
Sign up to set email alerts
|

Sonofragmentation of Molecular Crystals

Abstract: Possible mechanisms for the breakage of molecular crystals under high-intensity ultrasound were investigated using acetylsalicylic acid (aspirin) crystals as a model compound for active pharmaceutical ingredients. Surprisingly, kinetics experiments ruled out particle-particle collisions as a viable mechanism for sonofragmentation. Two other possible mechanisms (particle-horn and particle-wall collisions) were dismissed on the basis of decoupling experiments. Direct particle-shock wave interactions are therefor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
144
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 149 publications
(148 citation statements)
references
References 42 publications
4
144
0
Order By: Relevance
“…72 Ultrasound also has effects on the process of crystallization (through increased nucleation, enhanced mass transport to the crystal surface, and sonofragmentation of larger crystals). 73 Sonication has been used to prepare nanostructured organic crystals, although reports of the formation of nanosized crystals in this area are uncommon; typical crystals produced in this way are of micron scale. 73 One example of the application of ultrasound to the preparation of nanocrystals is the preparation of cocrystals of 2(resorcinol) 2(4,4 0 -bpe), which can produce nanocrystalline cocrystals that exhibit single-crystal-to-single-crystal reactivity.…”
Section: à2mentioning
confidence: 99%
See 1 more Smart Citation
“…72 Ultrasound also has effects on the process of crystallization (through increased nucleation, enhanced mass transport to the crystal surface, and sonofragmentation of larger crystals). 73 Sonication has been used to prepare nanostructured organic crystals, although reports of the formation of nanosized crystals in this area are uncommon; typical crystals produced in this way are of micron scale. 73 One example of the application of ultrasound to the preparation of nanocrystals is the preparation of cocrystals of 2(resorcinol) 2(4,4 0 -bpe), which can produce nanocrystalline cocrystals that exhibit single-crystal-to-single-crystal reactivity.…”
Section: à2mentioning
confidence: 99%
“…73 Sonication has been used to prepare nanostructured organic crystals, although reports of the formation of nanosized crystals in this area are uncommon; typical crystals produced in this way are of micron scale. 73 One example of the application of ultrasound to the preparation of nanocrystals is the preparation of cocrystals of 2(resorcinol) 2(4,4 0 -bpe), which can produce nanocrystalline cocrystals that exhibit single-crystal-to-single-crystal reactivity. 74 Compared with conventional reprecipitation methods, crystals obtained via sonochemistry were smaller and more uniform in size.…”
Section: à2mentioning
confidence: 99%
“…Furthermore, the size of the product crystals can be significantly influenced by the specific seed crystal sizes (Beckmann, 2000;Aamir et al, 2010). Since the application of ultrasound to trigger de-agglomeration and crystal breakage has been already frequently applied and detailed studies are available (Kim et al, 2011;Zeiger and Suslick, 2011;Patel and Murthy, 2009;Marković et al, 2008;Ruecroft et al, 2005;Dennehy, 2003), a more detailed study regarding this effect is not the aim of this work. Our work to be described below rather focuses on studying systematically the influence of: (a) different inlet flow rates, (b) continuous generation of seed crystals using US, and (c) the initial seed size distribution on the CSD development in a conically shaped fluidized bed crystallizer.…”
Section: Introductionmentioning
confidence: 99%
“…This procedure removes most of the small particles that are attached and grown into the surface of large crystals, but does not break the agglomerates of equally sized particles. Earlier work by Zeiger and Suslick studied the effect of sonication on crystal slurries in order to identify the mechanism of crystal fragmentation by ultrasound [48,49]. They concluded that the interaction between particles and cavitation shockwaves is the primary cause for this phenomenon, while other potential sources such as interparticle, particle-horn and particle-wall collisions only marginally contribute in the fragmentation process.…”
Section: Ultrasound As Post-treatmentmentioning
confidence: 99%
“…In turn, this reduces the nucleation and growth kinetics, and hence the depletion of the solute concentration [57]. On the other hand, ultrasound increases the available surface area in the solution by formation of additional crystals, disruption of aggregates and sonofragmentation phenomena [48,49,[57][58][59]. Disabling the ultrasonic field will thus reduce these effects, affecting the desupersaturation profile.…”
Section: Targeted Ultrasonic Treatment At Seeding Temperaturementioning
confidence: 99%